Langerhans cell histiocytosis of the sphenoid sinus: a case report - Yu, Guohua; Huang, Fei; Kong, Lingling; Kong, Xiangmei; Zhang, Luping; Xu, Qing (The Turkish Journal of Pediatrics, 2010)
Langerhans cell histiocytosis (LCH), previously known as histiocytosis X, is a rare disorder characterized by clonal proliferation and excess accumulation of pathologic Langerhans cells causing local or systemic effects. Bone is the most common organ involved and a single skull lesion is the most frequent presentation of childhood LCH. However, sphenoid sinus is an uncommon condition of involvement in LCH. Here we report a case of LCH in the sphenoid sinus, which occurred in a seven-year-old girl who presented initially with headache. The girl had suffered from headache for one month before she went to an otorhinolaryngologist one week before. Magnetic resonance imaging (MRI) showed a lesion of inflammatory granuloma. Surgery was performed and the disease was diagnosed pathologically as single-site LCH via hematoxylin-eosin (H&E) and immunohistochemical staining.